THE RELATIONSHIP BETWEEN NATIONAL TECHNOLOGICAL INITIATIVE OF TURKIYE AND TECHNOLOGICAL PLANNING - Keskin, Halit; Yilmaz, Tamer (TUBA-TURKISH ACAD SCIENCES, 2022)
Advancements in technology, national, and international forces, such as urbanization, migration, and cybersecurity concerns, have increased the vital importance of technology planning at both the organizational and national levels. Reduced product and technology lifecycles, increased R&D investments, more customized and complex products, and shortened periods between production and marketing of the products caused by technological progress have resulted in uncertainty, making the competition a struggling area for business organizations. When integrated with the overall business plan, technology strategy becomes an efficient tool for competitiveness. Technology planning has also been widely accepted as a significant impetus for national development. Although technological developments have led to prosperity for every society, the gaps between the well-being of societies continue to widen. Those gaps are primarily caused by technological disparity and are overcome through improving technology development capacity. Based on this, technology planning has become an instrument for policy counseling in most industrialized countries, particularly in developing ones. As in many developing countries, Turkiye is obliged to increase its innovation capacity by stimulating private and public R&D in sectors in which competitive pressures prevail to successfully maintain its national innovation and entrepreneurship ecosystem where participating institutions operate effectively. Turkiye needs to sustain its development in science, technology, and innovation and to focus on critical technologies to achieve its technological objectives in line with its 2023 vision.
Keywords: Technology planning; Technology acquisition; Technology exploitation; S&T policy; National development; INTEGRATING TECHNOLOGY; MANAGEMENT; FORESIGHT; INNOVATION; FRAMEWORK; Development Studies; Business & Economics; Science & Technology - Other Topics